MATEMATIKA FANINI O‘QITIShDA DIFFERENSIAL YONDAShUV SAMARADORLIGI - Xalknazarova, A.M. (SCIENCE and SOCIETY, 2025)
The article examines the effectiveness of a differentiated approach to teaching mathematics. The results of the study indicate the need for additional resources and teacher training to successfully implement the differentiated approach in the educational process.
Keywords: differential approach; mathematics education; independent thinking; individual needs; teaching methods; educational effectiveness